The practical guide to public inquiries - Mitchell, Isabelle (London, England : Zed Books, 2020)
"This practical guide provides legal practitioners, participants, witnesses and all those interested in the public inquiry process, stage-by-stage 'hands on' guidance to the process of public inquiries into matters of public concern. With its user-friendly format of summaries, checklists, 'top tips' and flow charts, this book, the first practical guide to public inquiries, provides guidance from the setting up of a public inquiry through to its close. It includes information on: - the appointment of the chairman and inquiry team; - the choice and significance of the venue; - the drawing up of inquiry procedures, protocols and rulings; - the appointment and role of core participants; - evidence taking; - conducting and attending hearings; - the role of experts; - the writing and publication of the inquiry report. Drawing on the authors' extensive experience as public inquiry lawyers, working on inquiries such as the Bloody Sunday Inquiry, Mid Staffordshire NHS Foundation Trust Inquiry, Leveson Inquiry and Grenfell Tower Inquiry, together with contributions from a number of other eminent practitioners in the field, this book provides valuable, comprehensive guidance on the public inquiry process"
Public inquiries -- Appointments -- Location and venue -- IT systems -- Protocols, rulings, directions and orders, and engagement with the media -- Core participants -- Funding -- Documentary evidence -- Data protection -- Evidence taking -- Oral evidence and hearings -- Assessors, seminars and experts -- Warning letters and Rules 13, 14 and 15 -- Preparing and publishing the report -- Closing down the inquiry.
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Keywords: Governmental investigations; Legislative auditing; Constitutional & administrative law; Electronic books